Perinephric Fat Stranding on Postmortem Computed Tomography Scan in Acute Pyelonephritis: A Case Report. (December 2019) - Garland, Jack; Olds, Kelly; Tse, Rexson
Abstract : Abstract: Infection/inflammation of solid organ can be difficult to appreciate at postmortem computed tomography (CT) scan (PMCT). Perinephric fat stranding is a clinical CT finding to suggest pyelonephritis; however, PMCT scan showing perinephric fat stranding in acute pyelonephritis has not been documented in the forensic literature. We present a death from acute pyelonephritis in a setting of hypertensive heart disease, in which the unenhanced PMCT performed before postmortem examination was able to show florid bilateral perinephric fat stranding. This PMCT finding subsequently guided the pathologist to pay special attention to the kidney and take appropriate microbiology specimens to confirm the diagnosis. Perinephric fat stranding on PMCT may be a useful sign to alert the pathologist to consider acute pyelonephritis during the postmortem examination.